The Development of Linktree Learning Media to Improve the Understanding of Main Idea of Narrative Text - Nafis, Olivia Zakkia; Nuryanto, Sukarir (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
Learning media plays a crucial role in enhancing the quality of education by serving as a tool for teachers to deliver material effectively. This study aims to develop Linktree-based learning media for Indonesian language instruction to improve students’ understanding of identifying the main idea in narrative texts for grade V at MI Guppi Jatimalang. The research employed a Research and Development (R&D) methodology, following the Borg and Gall development model. Data were collected through interviews, observations, documentation, and questionnaires distributed to teachers and students to assess their needs. Data analysis included feasibility and effectiveness testing of the learning media. The feasibility test results, based on expert validation, indicated scores of 89.2% from material experts and 88.4% from media experts, both categorized as “very feasible.” The effectiveness test, measured using N-Gain analysis, showed a result of 0.6076, placing it in the medium category. These findings suggest that the Linktree-based learning media is effective in supporting learning and enhancing students’ ability to identify the main idea in narrative texts. Its use is also expected to foster students’ motivation and critical thinking skills.